Economic and tourism indicators as a means of monitoring sustainable tourism: The case of inland Istria - Nikola Vojnovic; Rade Knezevic (UTMS Journal of Economics, 2013)
This paper analyses indicators to study the sustainability of tourism in inland Istria, which comprises 24 municipalities and towns belonging to Istria County. Taking into account the criteria of availability, reliability, predictability, clarity and feasibility, the following quantitative indicators were used: the Indicator of Tourist Operation (ITO), the Modified Importance Index of major tourism centres (Im), the Specific Overnights Threshold (SOT), tourism-related taxes in the budgets of municipalities and towns, company investments into tourism and hospitality, and the number of employees in tourism and hospitality. According to the ITO indicator, Predominant Tourism Activity was recorded only in Oprtalj Municipality. Being a measure of the spatial distribution of a specific economic activity, the Modified Importance Index established that in all municipalities and towns of inland Istria tourism is either poorly developed or in its incipient stage. The SOT indicator suggests that tourism has no negative effects on local economies and that tourism-related taxes make a minor contribution to the revenue side of municipal and town budgets. Company investment in tourism and hospitality and the number of employees in these industries are indicators that reveal that inland Istria is only beginning to develop into a tourism region. The quantitative indicators were confirmed by the results of qualitative indicators obtained through problem-focused interviews with the representatives of municipalities, towns and local tourist boards. The singular conclusion derived from the interviews was that tourism is a desirable activity, is in its initial stage of development, and is not a threat to local economies. The results of the study confirm the hypothesis that inland Istria is a region of sustainable tourism currently in the involvement stage of the destination lifecycle.
Keywords: Q01; 330; Inland Istria; municipalities and towns; sustainable tourism; monitoring; indicators; Croatia